Textbook reading strategies and its relationship to reading test performance - Lijuan Li; Sarjit Kaur (Penerbit Universiti Kebangsaan Malaysia, 2014)
Research studies on reading strategy use among ESL/EFL readers are increasingly becoming one of the most attended topics for researchers and educators. This study investigated the reading strategies used by 290 Chinese EFL second year undergraduates and examined the relationship between their reading strategy use and reading test performance. The participants reported their use of reading strategies through the Survey of Reading Strategies (SORS) in three categories: global reading strategies (GLOB), problem solving strategies (PROB) and support reading strategies (SUP). Students’ reading test performance was measured by using the national College English Test Band-4 (CET-4). Results showed that students used overall reading strategies at a medium frequency level. They used PROB strategies most frequently (at a high level), followed by GLOB strategies (at a medium level). The least frequently used were SUP strategies (at a medium level). The most frequently used individual strategies were re-reading, regaining concentration and guessing the content of the text. The least frequently used strategies included reading aloud, questioning, paraphrasing, and translating. There was no significant relationship between students’ overall reading strategy use and their general reading test performance. However, significant relationship was found between some individual reading strategies and different test formats. Students’ banked cloze test performance was positively correlated to GLOB strategies. SUP strategies were negatively correlated to students’ skimming and scanning performance. Most PROB strategies were related to student performance in fast reading either positively or negatively. Pedagogical implications are discussed in relation to the Chinese EFL context.